Graph Polynomial Approach for Some Molecules in H1N1 Antiviral Drugs - S. PARAMESWARI; K. BALASANGU (Utilitas Mathematica, 2025)
This study explores the potential of topological indices for oseltamivir and zanamivir, two common antiviral drugs. Topological indices are numerical descriptors of a molecule's structure, often used in drug discovery to predict various physical and chemical properties. We will calculate several polynomial-based indices for these drugs and analyse their relationship with their known physicochemical properties using linear regression. This analysis can provide insights into how a drug's structure influences its behaviour.